DRAGON IN CULTURAL EXPRESSIONS IN THE VICEROYALTY - Ordoñez Avalos, Marlene Mirtha (2011)
The contact with other places, like the old world and the Far East, brought new figures and concepts that were difficult to incorporate into the worldview of the Peruvian population. The dragon was one of these images that for the native, was associated with the serpent, a pre-existing and widely used by ancient cultures of this land. We see how this figure is akin to the dragon, which was used by the religious in their indoctrination of the Indians, being represented and mentioned in many cultural expressions in the Viceroyalty, as in painting, thearter and dance, giving a meaning evil.